RHEB gene therapy maintains the chondrogenic characteristics and protects cartilage tissue from degenerative damage during experimental murine osteoarthritis. Issue 10 (October 2019) - Ashraf, S.; Kim, B.J.; Park, S.; Park, H.; Lee, S.-H.
Summary: Objective: Osteoarthritis (OA) is characterized by cartilage degeneration resulting from hypertrophic changes in chondrocytes caused by altered gene expression. The involvement of Ras homolog enriched in brain (RHEB) in OA regulation is unclear. Methods: Human knee articular cartilage samples - were analyzed for structural and biological changes by histology, immunohistochemistry, real time PCR and western blotting. OA-mouse model developed by surgical destabilization of the medial meniscus (DMM) were treated with adenovirus harboring Rheb gene to analyze onset and progression of OA. Histological scoring, immunohistochemistry, and TUNEL assay was performed to assess cartilage damage across the entire joint. Results: Human and mouse OA cartilage is degenerated and has markedly reduced levels of RHEB. Human OA-degenerated chondrocytes (DC) exhibited a fibroblastic phenotype and 80 % of degenerative cartilage were senescent, with higher levels of reactive oxygen species (ROS). Gene expression analysis of DC revealed almost no COL2A1 expression and reduced SOX9 and RHEB expression. Transient transfection of RHEB rescued the DC phenotype and reduced senescence and ROS levels markedly. RHEB overexpression also increased COL2A1 and SOX9 expression. In an OA-mouse model, the Rheb protein level decreased as the severity of OA increased. Ectopic expression of Rheb using adenovirus in mouse-OA cartilage suppressed surgically-induced OA pathogenesis accompanied by modulation of Adamts5, Mmp 13, Col 10, and Col2a1 expression. Rheb induction significantly reduced apoptosis in OA-cartilage. Conclusion: RHEB plays an important role in maintaining the chondrogenic characteristics of chondrocytes, and has potential in preventing progression of OA in the destabilize the medial meniscus (DMM) mouse model of OA.